2006
DOI: 10.4049/jimmunol.177.9.6504
|View full text |Cite
|
Sign up to set email alerts
|

Immunization with an Apoptotic Cell-Binding Protein Recapitulates the Nephritis and Sequential Autoantibody Emergence of Systemic Lupus Erythematosus

Abstract: The initial events predisposing to loss of tolerance in patients with systemic lupus erythematosus (SLE) are largely unknown, as are the events that precipitate the transition from preclinical to overt disease. We hypothesized that induction of murine SLE would require tipping the balance between tolerance and immunity in two ways: 1) an immunogen that could take advantage of apoptotic cells as a scaffold for epitope spread, and 2) an immune activator that would generate a strong and persistent T cell response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
80
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(80 citation statements)
references
References 39 publications
0
80
0
Order By: Relevance
“…An earlier study has shown that anti-␤ 2 GPI responses spread rapidly to Ro 60 in mice immunized with ␤ 2 GPI, providing a clue that these autoantigens may be present as a complex on the apoptotic cell surface (15). In this study, we demonstrate that ␤ 2 GPI binds to an exposed region of Ro 60 on apoptotic cells and masks the Ro 60 apotope, thereby preventing the formation of IgG-apoptotic cell complexes.…”
mentioning
confidence: 62%
See 1 more Smart Citation
“…An earlier study has shown that anti-␤ 2 GPI responses spread rapidly to Ro 60 in mice immunized with ␤ 2 GPI, providing a clue that these autoantigens may be present as a complex on the apoptotic cell surface (15). In this study, we demonstrate that ␤ 2 GPI binds to an exposed region of Ro 60 on apoptotic cells and masks the Ro 60 apotope, thereby preventing the formation of IgG-apoptotic cell complexes.…”
mentioning
confidence: 62%
“…Previous studies using soluble MaBP fusion proteins expressing fragments of Ro 60 have identified an apotope within the aa 82-244 region (19). Given the relationship between Ro 60 and ␤ 2 GPI in experimental autoimmunity (15) and the ability of these lupus autoantigens to bind cognate autoantibodies on the surface of apoptotic cells (4,11), we investigated whether MaBP-Ro 60 aa 82-244 interacts with ␤ 2 GPI in direct binding experiments. MaBP-Ro 60 aa 82-244 bound to immobilized ␤ 2 GPI in a dose-dependent manner, while no significant binding was observed with an MaBP control ( Figure 1A).…”
Section: Resultsmentioning
confidence: 99%
“…It is reported that the prevalence of aPL in SLE cohorts varies from 20 to 50%, and patients with primary APS may subsequently evolve towards SLE, implying a strong interplay between APS and SLE (Tincani et al, 2009). Levine et al (2006) proposed a murine model of SLE involving TLR4 in the origin of aPL antibodies, which is somewhat analogous to Buttari' hypothesis. They showed that in C57BL/6 and BALB/c mice immunized with human b2GPI, which is not only a phospholipid-binding protein in APS but also an apoptotic cell-binding protein and one of the first autoantigens targeted in SLE, LPS induced a long-lived, potent immune response to b2GPI in the presence of TLR4 ligand that resulted in epitope spread to multiple SLE autoantigens, and the development of lupus-like glomerulonephritis (Levine et al, 2006).…”
Section: Tlr4 Hypothesis In Autoantibody Productionmentioning
confidence: 84%
“…Levine et al (2006) proposed a murine model of SLE involving TLR4 in the origin of aPL antibodies, which is somewhat analogous to Buttari' hypothesis. They showed that in C57BL/6 and BALB/c mice immunized with human b2GPI, which is not only a phospholipid-binding protein in APS but also an apoptotic cell-binding protein and one of the first autoantigens targeted in SLE, LPS induced a long-lived, potent immune response to b2GPI in the presence of TLR4 ligand that resulted in epitope spread to multiple SLE autoantigens, and the development of lupus-like glomerulonephritis (Levine et al, 2006). Based on these observations, they hypothesized that antigen-presenting cells (APCs) interact with LPS via TLR4, leading to APC activation and the generation of multiple proteins that contribute to inflammation and enhance adaptive immunity.…”
Section: Tlr4 Hypothesis In Autoantibody Productionmentioning
confidence: 99%
See 1 more Smart Citation